Predicting Selective RNA Processing and Stabilization Operons in Clostridium spp. - Bhaskar, Yogendra; Su, Xiaoquan; Xu, Chenggang; Xu, Jian (Frontiers in Microbiology, 2021)
In Selective RNA Processing and Stabilization (SRPS) operons, stem loops (SLs) located at the 3’ UTR region of selected genes can control the stability of corresponding transcripts and determine the stoichiometry of the operon. Here for such operons, we developed a computational approach named SLOFE (Stem-LOop Free-Energy) that identifies the SRPS operons, and predicts their transcript- and protein-level stoichiometry at the whole-genome scale using only genome sequence, via the minimum free energy (∆G) of specific stem-loops (SLs) in the intergenic regions within operons. As validated by the experimental approach of differential RNA-Seq, SLOFE identifies genome-wide SRPS operons in Clostridium cellulolyticum with 80% accuracy, and reveals that the SRPS mechanism contributes to diverse cellular activities. Moreover, in the identified SRPS operons, SLOFE predicts the transcript- and protein-level stoichiometry, including those encoding cellulosome complexes, ATP synthases, ABC transporter family proteins and ribosomal proteins. Its accuracy exceeds existing in silico approaches, in C. cellulolyticum, C. acetobutylicum, C. thermocellum and Bacillus subtilis. The ability to identify genome-wide SRPS operons and predict their stoichiometry via DNA sequence in silico should facilitate studying the function and evolution of SRPS operons in bacteria.